Potensi dan strategi pengelolaan berkelanjutan mata air Sikumbang di Desa Pulau Sarak Kecamatan Kampar Kabupaten Kampar - Arif Hidayatullah; Rifardi Rifardi; Sigit Sutikno (Pelantar Press, 2020)
In 2019 there were 9 (nine) managers of drinking water from Sikumbang Springs. The management of the Sikumbang Spring water supply business is still carried out individually and traditionally means that the management carried out by the Sikumbang Spring entrepreneur is only limited to exploitation. Management does not include environmental preservation. The purpose of this study was to determine the potential and determine the sustainable management strategy of Sikumbang Springs in Pulau Sarak Village, Kampar District, Kampar Regency. The benefit gained from this research is the balance between environmental, economic and social aspects in managing Sikumbang Spring. and the community as water users / entrepreneurs get information on the potential of Sikumbang Springs in Pulau Sarak Village. Analysis of the projected population of each village in the Kampar subdistrict above can be calculated the number of residents who use clean water. The more accurate results of the largest population is at the end of the planned year, namely in 2029 with a total population of 50.732 people (10-year projection). The potential of Sikumbang Spring based on the value of its debit from March to December 2020 is 247.127.040 liters. The need for clean water for household needs (drinking and cooking water) in Kampar sub-district is 6,3 ((liters / day) / soul), so that the community's water demand in Kampar sub-district in 2019 is 310.697 liters / day. The average daily debit of Sikumbang Springs is 808.272 liters / day. The calculation of the average daily debit of Sikumbang Spring shows that the debit value of Sikumbang Spring exceeds the value of its needs. Therefore, Sikumbang Springs in the study area can be used as an alternative in meeting the water needs of the local community and communities outside Pulau Sarak Village. Based on the results of the SWOT analysis of the management of the Sikumbang Spring, the strategy that can be applied is an aggressive (development) strategy that is maximizing strengths and taking advantage of available opportunities, so as to minimize weaknesses and avoid threats. Sikumbang Spring management must optimize the main function of Sikumbang Spring as a source of clean water in meeting household water needs and improving its marketing system. The role of the community in maintaining and preserving the source of the Sikumbang Spring also needs to be enhanced.